The Prisoners' Dilemma and Political Systems: The Impact of Proportional Representation on Criminal Justice in New Zealand - Lacey, Nicola (Victoria University of Wellington Law Review, 2011)
This is the text of the 2010 Shirley Smith Address delivered by Nicola Lacey on 8 December 2010, organised by the Wellington Women in Law Committee. The lecture offers an analysis of why New Zealand has attached itself to increasingly punitive criminal justice policies over the last 25 years, and considers in particular how far this has to do with the shape of New Zealand’s political system.